Profile Analysis of Fatty Acids of Tengkawang (Shorea Sumatrana) Oil Using GC-MS and Antibacterial Activity - Riski, Diah Gusti; Maulana, Rico Gewana Resdy; Permana, Edwin; Lestari, Intan; Tarigan, Indra Lasmana (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The Shorea sumatrana (tengkawang) plant is endemic to Indonesia, especially in Kalimantan and Sumatera regions, which produces chemical diversity especially as a natural drugs. Specific aims to investigate both the profile analysis of fatty acid and antibacterial potential of tengkawang oil. The extract of tengkawang oil was carried out using the soxhlet extraction method. The profile analysis of fatty acid was verified by GC-MS and the antibacterial activity was evaluated using disc-diffusion method. The profile analysis of fatty acid of tengkawang oil indicated the presence of palmitic acid (17.26%), stearic acid (60.68%), oleic acid (11.98%), oleic acid chloride (1.80%), stearic acid chloride (1.86%), glycidyl stearate (1.92%), diethyl phthalate (4%), and 2-monopalmitin (0.5%). We determined the antibacterial activity by the diameter of inhibition of growth zone against Salmonella enteritidis, Escherichia coli, Staphylococcus aureus, and Bacillus cereus at a concentration of 12.5%, 25%, 50%. These were compared with standard tetracycline as positive control and DMSO was assigned negative control. It was found that the highest percentage of fatty acid in tengkawang oil is stearic acid, at 60.68%, and that tengkawang oil is an antibacterial agent with a concentration optimum at 25% with more susceptibility to Gram-positive than Gram-negative bacteria.